Identification of Gram-Negative Bacteriuria among Diabetes Mellitus Patients at X Public Health Center, Kediri - TRIFFIT IMASARI; Erawati; Siska Kusuma Wardani; Indra Fauzi Sabban; Vanda Pitasari (Fakultas Sains, Teknologi, dan Analsisi Institut ilmu Kesehatan Bhakti Wiyata, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disorder characterized by a steadily increasing prevalence both globally and nationally. Patients with DM are highly susceptible to various infections, with Urinary Tract Infection (UTI) being one of the most frequent complications. The hyperglycemic state in DM patients leads to glycosuria, a condition where the presence of glucose in the urine creates an ideal environment for the proliferation of pathogenic microorganisms. Microbiologically, Gram-negative bacteria are the primary etiology of UTIs in diabetic patients. Bacteria such as Escherichia coli, Klebsiella pneumoniae, and Proteus mirabilis possess specific virulence factors that facilitate adherence to the urinary tract epithelium. The objective of this research was to identify Gram-negative bacteria and determine their percentage distribution among Diabetes Mellitus patients at Public Health Center X in Kediri. This research employed a descriptive research method with an accidental sampling technique, utilizing 14 urine specimens from DM patients. The results revealed the presence of Klebsiella sp. (36%), Escherichia coli (50%), and Salmonella sp. (14%) in the urine of the subjects. Based on these findings, it can be concluded that urinary tract infections in Diabetes Mellitus patients at Public Health Center X, Kediri, are caused by several types of pathogenic bacteria, with the highest prevalence being Escherichia coli, followed by Klebsiella sp., Salmonella sp., and Proteus sp. Early detection and management of bacterial infections are essential to prevent further complications in patients with Diabetes Mellitus